2021
DOI: 10.3389/fnagi.2020.587104
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Metabolite Concentrations Are Associated With Cortical and Subcortical Volumes and Cognition in Older Adults

Abstract: BackgroundCerebral metabolites are associated with different physiological processes in brain aging. Cortical and limbic structures play important roles in cognitive aging; however, the relationship between these structures and age remains unclear with respect to physiological underpinnings. Regional differences in metabolite levels may be related to different structural and cognitive changes in aging.MethodsMagnetic resonance imaging and spectroscopy were obtained from 117 cognitively healthy older adults. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Changes in the cerebral levels of those metabolites, following a fatty diet, have been reported in preclinical studies 21 and evidence exists that the consumption of a high caloric diet also leads to high concentrations of inflammatory cytokines in the brain, resulting in microgliosis, astrocytosis and neuronal damage 8 , 22 . Moreover, patients suffering from steatohepatitis have a reduced brain volume 23 and are at higher risk to suffer from neurological diseases, which are, most probably, related to the volume reductions as well 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the cerebral levels of those metabolites, following a fatty diet, have been reported in preclinical studies 21 and evidence exists that the consumption of a high caloric diet also leads to high concentrations of inflammatory cytokines in the brain, resulting in microgliosis, astrocytosis and neuronal damage 8 , 22 . Moreover, patients suffering from steatohepatitis have a reduced brain volume 23 and are at higher risk to suffer from neurological diseases, which are, most probably, related to the volume reductions as well 24 .…”
Section: Introductionmentioning
confidence: 99%
“…As neurochemical changes may serve as a precursor to atrophy, it would follow that certain areas are more vulnerable to age-related metabolic changes than others. An investigation of the relationships between cerebral metabolites and both cortical and subcortical brain volumes in the same sample has recently been published and found divergent relationships between frontal and parietal metabolite concentrations and cortical and subcortical brain volumes (Williamson et al, 2021 ). Additionally, in many cases, cytokines are pleiotropic or act on each other which further complicates the interpretation of seemingly counterintuitive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical thickness in the parietal region in CW appears to be larger than in CM [17]. As TM and CW show a similar developmental pattern in the parietal cortex [13,17], and because we expect volumetric changes to be reflected in altered metabolite concentration [58], we hypothesized that no differences exist between CW and TMGD regarding absolute metabolite levels and relative metabolite ratios in the parietal cortex. In the amygdala however, no volumetric differences have been reported in TM with respect to cisgender people.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Williamson et al (2021) examined the relationship between cerebral metabolites, brain volume, and cognitive performance [58]. They found that cerebral metabolite concentrations are associated with cortical and subcortical volumes.…”
Section: Introductionmentioning
confidence: 99%